Empirical modelling, simulation and control of coffee brewing - Taip, F.S.; Abdul Ghani, N.H.; Othman, N. (Rynnye Lyan Resources, 2024)
Coffee brewing is a complex process governed by various parameters such as water temperature, extraction time and particle size of ground coffee. These parameters affect the brewed coffee's quality in terms of flavour and aromatic compounds intensity. This research focused on studying the effect of water temperature on caffeine concentration in brewed coffee. It is done by changing the parameter of water temperature (80, 85, and 90°C). In contrast, other parameters such as type of coffee (Arabica), coffee particle size (500 µm), and coffee water ratio were kept constant. The results showed that the concentration of caffeine in the brewed coffee was increased as the water temperature increased. The highest concentration of caffeine was found at 90°C with 1084.35 ppm. An empirical model to study the effect of temperature in brewing process was developed. The model can be represented as first order model with time delay (FOPTD). The model was simulated and controlled using PI controller tuned using different methods. Performance and robustness analysis were done. In conclusions, the effect of water temperature on caffeine is determined, the coffee brewing model at different water temperatures was developed and simulated into different tuning rules of PI controller.